Wayfinding Tools for People With Visual Impairments in Real-World Settings: A Literature Review of Recent Studies - Parker, Amy T.; Swobodzinski, Martin; Wright, Julie D.; Hansen, Kyrsten; Morton, Becky; Schaller, Elizabeth (Frontiers in Education, 2021)
Abstract A literature review of 35 peer reviewed articles dated from 2016 to February, 2021 was conducted to identify and describe the types of wayfinding devices that people who are blind, visually impaired or deafblind use while navigating indoors and/or outdoors in dynamic travel contexts. Within this investigation, we discovered some characteristics of participants with visual impairments, routes traveled, and real-world environments that have been included in recent wayfinding research as well as information regarding the institutions, agencies, and funding sources that enable these investigations. Results showed that 33 out of the 35 studies which met inclusionary criteria integrated the use of smart device technology. Many of these devices were supplemented by bluetooth low energy beacons, and other sensors with more recent studies integrating LIDAR scanning. Identified studies included scant information about participants' visual acuities or etiologies with a few exceptions which limits the usability of the findings for this highly heterogeneous population. Themes derived from this study are categorized around the individual traveler’s needs; the wayfinding technologies identified; the contexts and routes for wayfinding tasks; and the institutional support offered for sustaining wayfinding research.